Enhanced Perfusion During Advanced Life Support Improves Survival With Favorable Neurologic Function in a Porcine Model of Refractory Cardiac Arrest. Issue 5 (May 2015) - Debaty, Guillaume; Metzger, Anja; Rees, Jennifer; McKnite, Scott; Puertas, Laura; Yannopoulos, Demetris; Lurie, Keith
<x xml:space="preserve">Abstract</x> Objective: To improve the likelihood for survival with favorable neurologic function after cardiac arrest, we assessed a new advanced life support approach using active compression-decompression cardiopulmonary resuscitation plus an intrathoracic pressure regulator. Design: Prospective animal investigation. Setting: Animal laboratory. Subjects: Female farm pigs (n = 25) (39 ± 3 kg). Interventions: Protocol A: After 12 minutes of untreated ventricular fibrillation, 18 pigs were randomized to group A—3 minutes of basic life support with standard cardiopulmonary resuscitation, defibrillation, and if needed 2 minutes of advanced life support with standard cardiopulmonary resuscitation; group B—3 minutes of basic life support with standard cardiopulmonary resuscitation, defibrillation, and if needed 2 minutes of advanced life support with active compression-decompression plus intrathoracic pressure regulator; and group C—3 minutes of basic life support with active compression-decompression cardiopulmonary resuscitation plus an impedance threshold device, defibrillation, and if needed 2 minutes of advanced life support with active compression-decompression plus intrathoracic pressure regulator. Advanced life support always included IV epinephrine (0.05 μg/kg). The primary endpoint was the 24-hour Cerebral Performance Category score. Protocol B: Myocardial and cerebral blood flow were measured in seven pigs before ventricular fibrillation and then following 6 minutes of untreated ventricular fibrillation during sequential 5 minutes treatments with active compression-decompression plus impedance threshold device, active compression-decompression plus intrathoracic pressure regulator, and active compression-decompression plus intrathoracic pressure regulator plus epinephrine. Measurements and Main Results: Protocol A: One of six pigs survived for 24 hours in group A versus six of six in groups B and C (p = 0.002) and Cerebral Performance Category scores were 4.7 ± 0.8, 1.7 ± 0.8, and 1.0 ± 0, respectively (p = 0.001). Protocol B: Brain blood flow was significantly higher with active compression-decompression plus intrathoracic pressure regulator compared with active compression-decompression plus impedance threshold device (0.39 ± 0.23 vs 0.27 ± 0.14 mL/min/g; p = 0.03), whereas differences in myocardial perfusion were not statistically significant (0.65 ± 0.81 vs 0.42 ± 0.36 mL/min/g; p = 0.23). Brain and myocardial blood flow with active compression-decompression plus intrathoracic pressure regulator plus epinephrine were significantly increased versus active compression-decompression plus impedance threshold device (0.40 ± 0.22 and 0.84 ± 0.60 mL/min/g; p = 0.02 for both). Conclusion: Advanced life support with active compression-decompression plus intrathoracic pressure regulator significantly improved cerebral perfusion and 24-hour survival with favorable neurologic function. These findings support further evaluation of this new advanced life support methodology in humans.